PESANTREN'S EDUCATION STRATEGY IN IMPROVING SANTRI'S LIFE SKILLS AT DARUS’SAADAH ISLAMIC BOARDING SCHOOL - Fatihatu Nurul Ulya; Ashif Az Zafi (Universitas Islam Sultan Agung, 2021)
Like in general, Islamic boarding schools only provide education to students with religious knowledge and morals as the main substance but do not provide the students with skills. As a result, the Pondok Pesantren alumni arose in their hearts a feeling of not mastering their skills when they brought them to their hometowns. Given such a situation, providing life skills is expected to be an alternative to this problem. This study provides an overview of what strategies are applied in implementing life skills education at the Darussa'adah Jekulo Kudus Islamic boarding school. This research uses a field case study. The data collection technique was used by pins in the form of observation methods, interviews with informants, and documentation. While the data analysis technique used is descriptive qualitative analysis techniques. This research was conducted at the Darussa'adah Hadipolo Jekulo Kudus Islamic boarding school. The results showed that the strategies used in improving life skills education ran quite effectively and yielded results. These results can be seen from the material presented by the management and caregivers and the high enthusiasm of all students in carrying out gardening and entrepreneurship activities owned by the Islamic Boarding School. The strategies used in developing entrepreneurial skills at the Darussa'adah Islamic Boarding School were quite successful, as evidenced by the development of plantations and entrepreneurship belonging to the Islamic Boarding Schools.Keywords: Education, Life Skill, Islamic Boarding School